CURRICULUM IMPLEMENTATION DURING COVID-19 PANDEMIC IN SOCIOLOGICAL PERSPECTIVE - Windu Widagdo; Isa Anshori (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
Since the appearance of the positive cases COVID-19 for the first time in Indonesia in March 2020, the number of confirmed positive cases and deaths has continued to increase to this day. The Covid-19 pandemic has had a systemic impact on all aspects of life, especially in education sector. In the event of a disaster emergency, education must continue with access and education services carried out in accordance with the conditions and centered on the fulfillment of children's educational rights and educational services carried out online. Based on this, the government has switched the learning and teaching process, which was originally in school to be at home or Home Study (BDR). In implementing this government policy, it is necessary to implement the school curriculum during the COVID-19 pandemic. This research aims to find out the curriculum implementation during covid-19 pandemic in sociological perspective. The research method used is qualitative method, this was to find information on curriculum implementation in the form of planning, implementation and assessment of curriculum at Muhammadiyah 1 Sidoarjo Junior High School during the covid-19 pandemic. The results obtained from this research, that is the implementation of the curriculum is very important in regulating learning during the covid-19 pandemic that must continue to run despite the social distancing implementation.